Notes to Philosophy 167: Class 10 -- Huygens and the Beginnings of Rational Mechanics -- Complete. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Science in the Thirty Years after Galileo's Death -- Huygens on Motion Under Perfectly Elastic Impact -- Huygens on Circular Motion and Centrifugal Force -- Huygens on the Center of Oscillation: Real Pendulums -- "Rational Mechanics": in the Tradition of Huygens.; Section: Class 10, Complete.